Ammonia alum hydrate-based phase change materials for effective use of excess exhaust heat from gas engines. (April 2019) - Nakamura, Kohei; Ina, Takashi; Suzuki, Hiroshi; Hidema, Ruri; Komoda, Yoshiyuki
Highlights: Ammonia alum hydrate-based novel phase change materials (PCMs) were prepared. The PCMs stored latent heat in the temperature range between 80 °C and 90 °C. A heat storage tank containing the PCM and hot water was prepared. The PCM in the tank stored and released more than 400 MJ·m −3 of heat. Abstract: For effective use of excess exhaust heat from gas engines, novel PCMs were prepared by adding anhydrous sodium sulfate andD -mannitol to ammonia alum hydrate. They melted and stored latent heat at the temperature range of exhaust heat from gas engines (around 90 °C). Heat storage and release characteristics of the novel PCMs were investigated with a heat storage tank containing hot water and the novel PCMs packaged into resin bags. As a result, the novel PCMs stored and released more than 400 MJ·m −3 of heat at the temperature range between 80 °C and 90 °C. The amount of heat storage and release by the PCMs was approximately ten times higher than that of water with same volume. This result indicates that the novel PCMs can reduce the volume of hot water tank dramatically in addition to storing and releasing exhaust heat from gas engines.